Theoretical issues and practical aspects of tax mechanisms of corruption counteraction - Z. S. Yakupov (Russian Journal of Economics and Law, 2014)
Objective: to view the existing and new mechanisms of corruption counteraction in the sphere of tax control. Methods: logical and statistical method, deduction and induction, scientific abstraction. Results: basing on the analysis of institutions of corruption and tax control, represented in the works of the Russian and foreign specialists, the author grounds the provision that successful corruption counteraction can be achieved only by mutual efforts of state and non-state controlling bodies within the frameworks of state-private partnership. Scientific novelty: Basing on the provision that the actual corruption counteraction is possible only with the participation of institutions and organizations of civil society, the author proposes ways of improving tax control connecting the advantages of state tax control and possibilities of non-state controlling bodies. For the first time the model of tax control institution participation in corruption counteraction is proposed. Practical value: possibility to increase the efficiency of tax mechanism of corruption counteraction by attracting auditor and consulting organizations to tax control.